The Effect of Sodium Propionate on Microorganism and Self life of Laboratory Biscuit - Baghdad Science Journal (مجلة بغداد للعلوم)
This study has been conducted to examin the effect of sodium propionate at different level of 0.03,0.06,0.10% on the number of bacteria and mold and to extend the storage life of laboratory processed biscuit. The results indicated that the use of 0.10% sodium propionate prolonged the storage peroid until the third month, while the use of 0.20% sodium propionate showed no growth of bacteria up to six month of storage, three types of bacteria has been isolated from processed biscuit, namely, Staphylococcus aureus, Bacillus cereus, Esherichia coli. using 0.10% sodium propionate showed no growth of mold up to three month of storage ,while using of 0.15 % and 0.20% sodium propionate prevent the growth of mold up to five and six months of storage respectively, Penicillum sp ,Aspergillus terrius, Aspergillus niger, flavus Aspergillus were isolated from the processed biscuit.